HEPATOPROTECTIVE ACTION OF THYMALINUM AND SUSPENSION OF RED BONE MARROW IN TREATING EXPERIMENTAL TOXIC HEPATITIS OF RATS - E. F. Kulbekov; Y. E. Kulbekova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Hepatic decompensation problems make it timely to search for the methods of its treatment. Stem cells usage in attempt to restore structures of organs and tissues is a promising direction of researches. However the problem of possible blast-cell transformation slows down studies in this direction. Attempt of thymalinum use as an antitumoral immune system's modulator may be successful and may widen the possibilities of stem cells use in hepatology. On the basis of toxical affection of rats' lever by tetrachloromethane and paracetamol we have studied hepatoprotective activity of thymalinum and suspension of rats' red bone marrow (RBM) and a thymalinum + suspension of RBM complex. Hepatoprotective action was estimated by the volume of discharged bile of control group rats which received paracetamol comparing with intact animals. This confirms the absence of reliable hepatotoxical action of paracetamol following the methodology applied. Significant reduction of discharged bile volume of control group rats which received tetrachloromethane comparing with intact animals confirms the successfulness of the formation method of hepatitis model in animals which received tetrachloromethane. The animals which were given tetrachloromethane and thymalinum + suspension of RBM combination had bigger volume of bile discharged than control group animals. Hepatoprotective action tendency of thymalinum + suspension of RBM combination shown before on mice is also true for rats.